Fausto como teatro de animação - Tavares, Pedro Heliodoro de Moraes Branco (In:Pandaemonium Germanicum;São Paulo : Departamento de Letras Modernas, Faculdade de Filosofia, Letras e Ciências Humanas, Universidade de São Paulo, 1997-;Band 18 (2011), Seite 72-99;Online-Ressource, 2011)
In this article we intend to present the history of Faust through the puppet theatre tradition and its influences on literary works concerning the heretic doctor. Based on a true character, the legend of Faust goes back to the time of Lutheran reform. Since Spies'
urn:nbn:de:hebis:30:3-262072
Keywords: Online-Publikation; Goethe; Johann Wolfgang von; Mann; Thomas; Spiess; Christian Heinrich; Faust; Doktor Faustus; Figurentheater; Faustdichtung